Women at Work in Preindustrial France - Hafter, Daryl M., 1935- (Book collections on Project MUSE., 2007)
The subject of women as skilled workers in the eighteenth century is central to our understanding of the history of work and technology in the preindustrial age. While recent scholarship has dispelled the notion that women did not enter the workforce until the Industrial Revolution, debate continues as to the extent to which women actually participated in skilled work in the preceding decades. This book draws upon substantial archival research in Rouen, Lyon, and Paris to show that while the vast majority of working women in eighteenth-century France labored at unskilled, low-paying jobs, it was not at all unusual for women to be actively engaged in economic activities as workers, managers, and merchants. Some even developed vertically integrated wholesale and retail businesses, while others became indispensable to manufacturers through their technical skill. In fact, Hafter documents how certain women guild masters were able to exploit the legal system to achieve considerable economic independence, power, wealth, and legal parity with male masters. She also shows how gender politics complicated the day-to-day experience of these working women.